Phrenic nerve neurotization using the spinal accessory nerve for diaphragmatic palsy in extensive high spinal cord injury secondary to idiopathic acute transverse myelitis - Antonio Heredia Gutierrez; Maria Eugenia Carbarin Carbarin; Samuel Torres García; Fernando Chico Ponce de Leon (Brazilian Society for Pediatric Neurosurgery, 2020)
The authors present a case of functional improvement of diaphragmatic paralysis in extensive high spinal cord injury, performing a neurotization of the phrenic nerve with the spinal accessory nerve. A C2-C5 injury of the spinal cord was diagnosed in a 15 years old female, secondary to idiopathic acute transverse myelitis. The patient did not have automatic respiration at the time of mechanical ventilation removal; moreover, she presented ventilatory distress. The neurotization of the left phrenic nerve with left spinal accessory nerve was performed 3 months after the injury, at six months after surgery she showed mobilization of the left hemidiaphragm and reached mechanical ventilation independence.